A STUDY ON TRACEABILITY AIMING AT PROCESS CONTROL - Silva, Anderson Rogério da; Gasparotto, Angelita Moutin Segoria (Revista Interface Tecnológica, 2020)
The objective of this article is to carry out a study on traceability aiming at the control of processes, from the observation, in a practical way, of the positive impacts caused by quality management, through a bibliographic research and a case study. In addition, to emphasize the importance of the identification and traceability system as a competitive differential and its application within a metallurgical company. It is suggested to use quality tools such as: control chart, 5W2H, PDCA cycle. However, the greatest emphasis is on an improvement proposal using the identification and traceability as a basis for the application of these tools mentioned above, to identify, through data collection and crossing, if any, correlation between the most frequent non-conformities of machined parts found on the assembly line and, elaborate an action plan in order to improve the control of the productive machining process, thus avoiding greater losses: financial, in the fulfillment of the delivery period, in the reorganization of the production schedule and, all disorders caused by non-conforming parts reaching the assembly line.